2020
DOI: 10.31195/ejejfs.712992
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of ten estimators for fitting two-parameter weibull function to Nigerian forest stands

Abstract: The quality fit produce by distribution function such as the Weibull depends to an extent the type of estimator used to derive its parameters. Inappropriate choice of estimator could affect management decision. Though several estimators have been developed for the Weibull function, their application to forestry have been relatively few. Therefore, this study evaluated ten estimators of the Weibull parameters using tree diameter data from five production forest plantations in Nigeria. The estimators were genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…(2019) also reported good fit with the Weibull function fitted by moment for characterising diameter distributions in uneven-aged mixed stands of pine and oak. In Nigeria, Ogana (2020) also observed that using moment-based estimator to fit the Weibull distribution produced results comparable to other complex estimators. The author evaluated ten estimators used for the Weibull distribution in the study.…”
Section: Resultsmentioning
confidence: 77%
“…(2019) also reported good fit with the Weibull function fitted by moment for characterising diameter distributions in uneven-aged mixed stands of pine and oak. In Nigeria, Ogana (2020) also observed that using moment-based estimator to fit the Weibull distribution produced results comparable to other complex estimators. The author evaluated ten estimators used for the Weibull distribution in the study.…”
Section: Resultsmentioning
confidence: 77%